Enterococcus faecium and Enterococcus faecalis in endodontic infections: antibiotic resistance profile and susceptibility to photodynamic therapy - Prado, Ana Carolina Chipoletti [UNESP]; De Barros, Patrícia Pimentel [UNESP]; Santos, Jéssica Diane Dos [UNESP]; De Oliveira, Luciane Dias [UNESP]; Carvalho, Claudio Antônio Talge [UNESP]; Valera, Marcia Carneiro [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2017)
Introduction: Enterococcus faecium has become an important microorganism in nosocomial infections with great ability to acquire antibiotic resistance. However, little is known about their presence on the oral cavity. Therefore, our objective was to verify the presence of E. faecium and E. faecalis in endodontic infections and compare their susceptibility to conventional antibiotics and photodynamic therapy. Methods: We performed 38 collections from the root canals of different patients. Positive Enterococcus agar samples were submitted to phenotypic and genotypic testing for species-specific confirmation. The isolates identified as E. faecium and E. faecalis were tested for susceptibility to antibiotics by the E-test method. After that, the isolates were evaluated for susceptibility to photodynamic therapy (PDT) using methylene blue and gallium arsenide aluminum laser with a wavelength of 660 nm and fluence of 39.5 J/cm2 (energy of 15 J and time of 428 s). Results: Cultures positive for E. faecalis were found in 22 patients (58%). Among these patients, only two had E. faecium in mixed infections with E. faecalis. In the isolates of E. faecalis, 27% were resistant to antibiotics, including tetracycline, ciprofloxacin, and azithromycin. The isolates of E. faecium showed no resistance to the antibiotics tested. Both the isolates of E. faecium and E. faecalis exhibit significant susceptibility to PDT, including the isolates resistant to antibiotics. The reductions achieved by PDT ranged of 2.76 to 4.31 log10 for E. faecalis strains and of 3.93 to 4.33 log10 for E. faecium strains. Conclusion: E. faecium showed lower prevalence in endodontic infections and higher susceptibility to antibiotics when compared to E. faecalis. In in vitro assays, PDT had a significant antimicrobial activity for both strains.
Keywords: Antimicrobials; Enterococcus faecalis; Enterococcus faecium; Photodynamic therapy